2021
DOI: 10.3390/biom11101483
|View full text |Cite
|
Sign up to set email alerts
|

Nostocyclopeptides as New Inhibitors of 20S Proteasome

Abstract: Nostocyclopeptides (Ncps) are a small class of bioactive nonribosomal peptides produced solely by cyanobacteria of the genus Nostoc. In the current work, six Ncps were isolated from Nostoc edaphicum strain CCNP1411. The bioactivity of these compounds was tested in vitro against 20S proteasome, a proteolytic complex that plays an important role in maintaining cellular proteostasis. Dysfunction of the complex leads to many pathological disorders. The assays indicated selective activity of specific Ncp variants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…For example, it has been shown that from the cyanobacterium Nostoc sp. isolated cyclic peptide nostocyclopeptide A exhibits antibacterial activity against several Gram‐positive bacteria (Fidor et al, 2021). Similarly, the cyclic peptide microcyclamide 7806A, produced by the cyanobacterium Lyngbya majuscula , has been shown to have potent activity against methicillin‐resistant Staphylococcus aureus (MRSA) (Dahiya et al, 2020).…”
Section: Marine Cyanobacteria As a Source Of Novel Antibioticsmentioning
confidence: 99%
“…For example, it has been shown that from the cyanobacterium Nostoc sp. isolated cyclic peptide nostocyclopeptide A exhibits antibacterial activity against several Gram‐positive bacteria (Fidor et al, 2021). Similarly, the cyclic peptide microcyclamide 7806A, produced by the cyanobacterium Lyngbya majuscula , has been shown to have potent activity against methicillin‐resistant Staphylococcus aureus (MRSA) (Dahiya et al, 2020).…”
Section: Marine Cyanobacteria As a Source Of Novel Antibioticsmentioning
confidence: 99%